Strategi Usaha Mikro Kecil Dan Menengah Dalam Menghadapi Inflasi (Studi Kasus Pada Warteg di Kota Semarang) - Muhammad Ricza Irhamni; Mutia Auliya Nisa; Yunia Milakhunnisa; Dimas Lukman Hakim (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The purpose of this study is to identify the potential and characteristics of MSMEs in Warung Tegal and to analyze internal and external factors as a business strategy for dealing with inflation. The data was analyzed using the strengths, weaknesses, opportunities, and threats (SWOT) method. MSMEs of Warung Tegal has the same characteristics in production, marketing, human resources, finance, law, and support from related agencies. In addition, its production uses a manual process, Warung Tegal sells its products through offline stores directly with 2-10 employees. Capital is relatively low and some MSME units of Warung Tegal have legality and well-managed management. Local governments play an important role in developing MSMEs in the face of inflation. Its main strength is the local supply of raw materials and the strategic location of the business, and the main drawback is the limited labor ability due to lack of training. The main opportunity is the trend of high public demand and openbusiness partnerships, but they also face fierce competition as the main threat. MSME strategies in dealing with inflation include increasing cooperation to maintain the continuity of raw materials between regions, developing MSME service innovations, and increasing the role of local governments.